Analyzing the Rapid Mixing Time Effect on Coagulation – Flocculation Process using Moringa Oleifera - Mutiara Fajar (Journal of Multidisciplinary Academic, 2020)
Rapid mixing time is one of the most important factors on coagulation – flocculation process in water treatment. In this study, Moringa Oleifera (MO) seed was used as a natural coagulant to remove Fe and Mn in well water. The effects of rapid mixing time to remove Fe, Mn, and turbidity floc size were investigated. Here, rapid mixing time variations were used around 30 -300 s coagulant doses (equal 33 mg/l) with 100 rpm rapid mixing speed while slow mixing speed of 40 rpm for 10 minutes and settling time for 60 minutes. The result showed that Fe and Mn removal ranging from 26-48 % and 13-31% with optimum rapid mixing time to remove Fe was 180 s; Mn was 150 s; and turbidity was 180 s, respectively. Based on correlation analysis using SPSS software with the Rank Spearman method, the residual concentration of Fe had a very strong correlation with residual Mn (r = 0.967) and a strong correlation with turbidity (r = 0.746) while the residual concentration of Mn has a very strong correlation with turbidity (r = 0.809).